Dampak Kebijakan Moneter terhadap Kinerja Sektor Manufaktur dan Ditinjau Secara Syariah - Dian Zahra Syahfitri Lubis; Fathiya Syahidah Nasution; Maulida Rahma; Maryam Batubara (Universitas Muhammadiyah Surabaya, 2024)
Monetary policy is a tool used by central banks that can influence financial variables such as interest rates and the amount of money in circulation. The goal is to protect the value of money from external and internal threats while maintaining its stability. This monetary policy has a big influence on various sectors, one of which is the manufacturing sector. The method used is qualitative research. By using library research in collecting data. The Monetary policy is a policy that determines interest rates in a country, in the manufacturing sector, this is of course very influential for industrial progress if accompanied by restrictions that can hinder company. If viewed from an Islamic perspective, sharia economics has no regulations or determination regarding interest rates, the use of monetary policy in manufacturing companies is certainly not sustainable if the company is a sharia manufacturer. Monetary policy can influence the manufacturing sector, such as controlling inflation and interest rates to form a positive impact on policy. In this monetary context, monetary policy must be handled carefully in the context of Sharia economics so that it is in accordance with Sharia principles and has a good impact, especially in terms of managing interest rates and inflation. In Indonesia, the industrial sector plays an important role in driving economic expansion.